Binding Functions of Microbe Cement1. Issue 3 (7th May 2014) - Rong, Hui; Qian, Chun‐Xiang
Abstract : Microbe cement as a new technique of consolidating loose particles has drawn much attention because of the ever increasing awareness of environmental protection. The technique relies on the microbial‐induced calcite precipitation at particle–particle contacts and around individual particles. In order to further explain the binding essence of microbe cement, this paper firstly compares the effect of cementing loose particles by microbial calcite cement with that by chemical precipitated calcite. Moreover, the morphology of calcite produced by above‐mentioned two methods and the microstructure between calcite and loose sand particles are analyzed by transmission electron microscope (TEM), infra‐red spectra (IR), X‐ray photoelectron spectroscopy (XPS), and nuclear magnetic resonance (NMR), respectively. The TEM results indicate that the microbial calcite consists of many fine grains with irregular shape, however, the chemical calcite has significant growth steps. The IR, XPS, and NMR results all show that the microbial‐induced precipitation of calcite in loose sand particles interacts with other particles to generate hydrogen bond, which play a role in binding function between loose sand particles and calcite produced by microbe cement. Abstract : The binding functions of microbe cement are researched by transmission electron microscope, infra‐red spectra, X‐ray photoelectron spectroscopy, and nuclear magnetic resonance. The results show that the binding essence of microbe cement is relied on the hydrogen bond between calcites produced by microbe cement and loose sand particles.